Analisis Kelayakan Usahatani Nanas (Ananas comosus) - Elvia Manisha; Yusmini Yusmini; Eliza Eliza (Jurnal Sosial Ekonomi Pertanian, 2023)
ABSTRACT This study aims to analyze the financial feasibility and sensitivity of increasing input prices, decreasing the amount of production, and decreasing output prices of Mr. Agus' pineapple farming in Sungai Kayu Ara Village, Sungai Apit District, Siak Regency. The research method used is a case study method, while the data used are primary data and secondary data, and the informant in this study is Mr. Agus with a land area of ​​2 hectares. Analysis of the data used to answer the research objectives are the investment criteria of Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), and Internal Rate of Return (IRR). The results show that pineapple farming is feasible because it has a positive NPV value of Rp.533.216.309, the Net B/C value is greater than zero, namely 5.85, and the IRR value is greater than the Social Opportunity Cost of Capital (SOCC) which is 78,89%. Pineapple farming is still feasible if there is an increase in fertilizer prices by 15%, a decrease in pineapple production by 10%, and a decrease in output prices by 25%. Keywords: Pineapple, financial feasibility, farming.